2021
DOI: 10.3390/cells10102608
|View full text |Cite
|
Sign up to set email alerts
|

A Human 3D Cardiomyocyte Risk Model to Study the Cardiotoxic Influence of X-rays and Other Noxae in Adults

Abstract: The heart tissue is a potential target of various noxae contributing to the onset of cardiovascular diseases. However, underlying pathophysiological mechanisms are largely unknown. Human stem cell-derived models are promising, but a major concern is cell immaturity when estimating risks for adults. In this study, 3D aggregates of human embryonic stem cell-derived cardiomyocytes were cultivated for 300 days and characterized regarding degree of maturity, structure, and cell composition. Furthermore, effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Here, the improved Ca 2+ current density, increased CaT amplitude, decreased CaT decay tau, and prolonged APD 90 observed in PC compared to RM may be due to enhanced ATP transport between SR and the sarcomere in PC, although further studies are needed to prove these links. Last, we also observed significantly increased multinucleation rates in iPSC-aCMs in PC (25 to 50%) compared to RM (10 to 20%), which may reflect the induction of cell cycle withdrawal ( 25 , 49 , 50 ). iPSC-aCMs in PC up-regulated the gene expression of cyclin-dependent kinase inhibitors, CDKN2A and CDKN2B , important for cell cycle withdrawal ( 49 ).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Here, the improved Ca 2+ current density, increased CaT amplitude, decreased CaT decay tau, and prolonged APD 90 observed in PC compared to RM may be due to enhanced ATP transport between SR and the sarcomere in PC, although further studies are needed to prove these links. Last, we also observed significantly increased multinucleation rates in iPSC-aCMs in PC (25 to 50%) compared to RM (10 to 20%), which may reflect the induction of cell cycle withdrawal ( 25 , 49 , 50 ). iPSC-aCMs in PC up-regulated the gene expression of cyclin-dependent kinase inhibitors, CDKN2A and CDKN2B , important for cell cycle withdrawal ( 49 ).…”
Section: Discussionmentioning
confidence: 53%
“…iPSC-aCMs in PC up-regulated the gene expression of cyclin-dependent kinase inhibitors, CDKN2A and CDKN2B , important for cell cycle withdrawal ( 49 ). Previous studies have shown that long-term culture (>100 days) was required to achieve iPSC-aCM bi/multinucleation ( 25 , 50 ), whereas iPSC-aCMs in PC achieved these outcomes in ~45 days, suggesting an accelerated maturation timeline useful for more timely execution of compound screening and disease modeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the applications of mathematical methods in cardiac research are much more wide-ranging, for example, for the analysis of population studies [41]. Moreover, currently in vitro cardiac models from stem cells are of great interest [42,43]. Such a system can also be studied using corresponding mathematical models [44].…”
Section: Discussionmentioning
confidence: 99%